Prototyping disruptive self-sufficiency power machines composed by cascaded power units based on thermo-hydraulic actuators - Ferreiro Garcia, Ramon (JOURNAL OF ADVANCES IN PHYSICS, 2024)
This research focuses on developing a prototype for a disruptive Self-Sustaining Power Machine (SSPM) that consists of cascaded power units (PUs). Each PU integrates thermo-mechanical and thermo-hydraulic actuators to drive hydraulic pumps connected to generators. The prototype’s design leverages two thermal cycle types, sVsVs and VsVs, which enable self-sustaining operations by employing several strategic capabilities that challenge the limitations of second-kind perpetual motion machines (PMMs). Therefore, key capabilities include: 1- Performing useful mechanical work through the expansion and contraction of the Thermal Working Fluid (TWF) by adding and removing heat. 2- Utilizing recovered heat through potential superposition techniques, thereby upgrading the heat to a higher grade, which enhances heat recovery strategies. 3- Designing an efficient energy transfer chain from thermal to electrical energy via thermo-mechanical or thermo-hydraulic actuators, a hydraulic energy drive system, and conversion from hydraulic to electrical energy. 4- Configuring the system to achieve more useful work than the heat added to the initial PU downstream. Two main prototype types are proposed to demonstrate these proposed capabilities: 1- Continuous motion using the sVsVs thermal cycle, with volumetric reservoirs for thermal working fluids (TWF) located outside the thermo-mechanical or thermo-hydraulic actuators. 2- Discontinuous motion using the VsVs thermal cycle, with volumetric reservoirs for TWF located inside the active volume of the thermo-mechanical or thermo-hydraulic actuators. The prototypes were evaluated through case studies using air and helium as real TWFs. Results indicate that the SSPM composed of five cascaded PUs operating on an sVsVs cycle achieved a global efficiency of 149.6% (SSI of 49.6%) with helium and 126% (SSI of 26%) with air. In contrast, the VsVs cycle yielded a global efficiency of 183% (SSI of 83%) with helium and 133% (SSI of 33%) with air